Beautiful blue world - LaFleur, Suzanne M. (Wendy Lamb Books, 2016)
Sofarende is at war and the army is paying families well to recruit children, so if twelve-year-old Mathilde or her best friend Megs is chosen, they hope to help their families but fear they will be separated forever.